Phonological Complexity in the Japanese Short Poetry: Coexistence Between Nearest-Neighbor Correlations and Far-Reaching Anticorrelations - Hayata, Kazuya (Frontiers in Physics, 2018)
The abstract is given on the first page in the revised manuscript.